2021
DOI: 10.1111/nhs.12812
|View full text |Cite
|
Sign up to set email alerts
|

Meals beyond the bedside: An ethnographic exploration of staffs' perspectives and experiences of communal dining in subacute care

Abstract: Communal dining offers multiple benefits for hospital patients, yet dining rooms may be underutilized in practice. This study aimed to understand and explore staffs' perspectives and experiences of communal dining in subacute care, and the impacts on staff mealtime practice. Using qualitative, ethnographic methodology, 94 hours of fieldwork were conducted across two subacute care wards. Participants were staff involved in nutrition care or present on the ward at mealtimes. Ninety‐one semistructured and ethnogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 36 publications
(57 reference statements)
0
9
0
Order By: Relevance
“…If the room is too far from the patient’s room, it might be difficult for the patient to reach it independently. This creates more workload for the nursing staff to transport patients from their room to the dining room [ 45 ]. In a study in the stroke rehabilitation context, the distance was found to play a role in patients’ mobility—patients were only independently visiting spaces close to their rooms [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…If the room is too far from the patient’s room, it might be difficult for the patient to reach it independently. This creates more workload for the nursing staff to transport patients from their room to the dining room [ 45 ]. In a study in the stroke rehabilitation context, the distance was found to play a role in patients’ mobility—patients were only independently visiting spaces close to their rooms [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, if communal dining areas for hospitalized patients are implemented, they should be within a distance where most patients can reach them independently. In addition to transporting patients, another challenge of communal eating is keeping careful supervision over all patients during mealtimes, as some patients cannot eat outside their rooms [ 45 ]. This could be alleviated by positioning the dining room centrally on the ward and allowing for easy supervision via a large window close to the nurses’ station [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…c Two wards reported on, however unable to distinguish systems used in each to report on separately. Three qualitative studies reported over seven papers (Baptiste et al, 2014;Jong et al, 2021;Ottrey et al, 2018Ottrey et al, , 2019Sidenvall, 1999;Sidenvall et al, 1994;Sidenvall et al, 1996) and one mixed-methods study (Mathiesen et al, 2021) discussed outcomes related to the eating environment (n = 8). Attitudes and perspectives, and actions and behaviours were explored in three studies each, and values and beliefs were explored in two studies.…”
Section: Discussionmentioning
confidence: 99%